PENGALAMAN ANAK DALAM MENGGUNAKAN UJARAN KASAR: STUDI FENOMENOLOGI INTERPRETATIF DI KOMUNITAS X KOTA PADANG - Huda Nabillah, Nurul; Kurniawan, Rizal; Santoso, Indriyani; Aulia, Rahmadianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to understand deeply the experiences of children in using profanity at the Community X in Padang City, West Sumatra. The phenomenon of children using offensive language is a complex issue influenced by multiple environmental factors. Employing a qualitative approach with Interpretative Phenomenological Analysis (IPA), this study involved three child participants aged 11 years, namely Vino, Manda, and Kevin, who are actively engaged in the community. Data were collected through in-depth semi-structured interviews conducted at the community site. The findings reveal three distinct patterns: Vino is aware that his behavior is inappropriate but feels powerless due to social group pressure; Manda demonstrates the highest moral awareness and the most concrete motivation for change, shaped by a painful relational experience; Kevin exhibits complete normalization of profanity with an absence of moral conflict and notably low empathy. All three participants were exposed to profanity from similar sources, namely family, physical environment, peers, and digital content, yet constructed meaning from those experiences very differently. The study confirms that normalization of profanity in children is not merely a character issue but a product of complex social ecology. Effective intervention requires a holistic approach simultaneously addressing family, peer group, and community dimensions.